2011
DOI: 10.5194/angeo-29-623-2011
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation of short-period (20–120 min) gravity waves in the equatorial Mesosphere and Lower Thermosphere and its relation to deep tropical convection

Abstract: Abstract. We study short period gravity waves (20-120 min) in the equatorial Mesosphere and Lower Thermosphere (MLT) using a Medium Frequency (MF) radar at Pameungpeuk (7.4 • S, 107.4 • E), Indonesia. In particular, we study local time and seasonal variation of the gravity wave variance and its relation to tropical convection. The gravity wave variance at 88 km enhances between 20:00 LT and 07:00 LT, with a peak at 02:00-03:00 LT. The enhancement is mainly observed during February-April and September-October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…reported that GWs could take ∼3-24 hr to reach the lower thermosphere. Venkateswara Rao et al (2011), on the other hand, suggested a time delay of ∼1-15 hr between the peak of deep convection and propagating GWs in the lower thermosphere. Therefore, it is possible that the convection of upward propagating GWs excited by tropospheric convection regions could be responsible for the changes observed in the Brazilian equatorial region on 28 June 2009.…”
Section: Discussionmentioning
confidence: 99%
“…reported that GWs could take ∼3-24 hr to reach the lower thermosphere. Venkateswara Rao et al (2011), on the other hand, suggested a time delay of ∼1-15 hr between the peak of deep convection and propagating GWs in the lower thermosphere. Therefore, it is possible that the convection of upward propagating GWs excited by tropospheric convection regions could be responsible for the changes observed in the Brazilian equatorial region on 28 June 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Using ray tracing analysis of gravity waves detected over Brasilia by an Airglow imager, Vadas et al [] showed that gravity waves could take ~3 to 24 h to reach dissipation altitudes (lower thermosphere). Using correlation between wind velocity measurements and convection activities over Indonesia, Venkateswara Rao et al [] suggested that the time delay between the peak of a deep convection and propagating gravity waves in the lower thermosphere could be ~1 to 15 h. Hence, we expect gravity waves generated by the tropospheric convection (north‐east and south‐west of São Luís, Figure ) to be able to modulate electrojet irregularities until ~16:00 UT (Figure a).…”
Section: Data Presentationmentioning
confidence: 98%
“…Between ~5:45 and 17:45 UT, strong convection activity happened within ~500 to 1000 km of São Luís. About 1 to 15 h would be sufficient for gravity waves to reach the E region [ Vadas et al , ; Venkateswara Rao et al , ]. Gravity waves generated from these convection sources could have obliquely propagated to the E region to cause the radar echo fluctuations (Figure d) and Δ H oscillations (Figure c).…”
Section: Data Presentationmentioning
confidence: 99%
“…It has been known for decades that convection in the troposphere is an important source for internal gravity waves in the lower and middle atmosphere, but while the mechanisms for the generation of topographic gravity waves have been studied extensively (e.g., Baines 1995;Wurtele et al 1996), the convective generation mechanisms are less well understood. Measurements and analyses quantify the relationship between convection and gravity waves in the troposphere and middle atmosphere (e.g., Pfister et al 1986;Tsuda et al 1990;Vincent and Alexander 2000;Alexander et al 2008;Dutta et al 2009) and in the upper atmosphere (e.g., Tsuda et al 1990;Kovalam et al 2006;Taylor et al 2009;Venkateswara Rao et al 2011). However, these analyses cannot give a complete description of internal gravity waves and their effects on the global circulation of the atmosphere; in particular, radar coverage is limited in location (Sato 1992), and aircraft observations provide limited information on the vertical structure of the waves (e.g., Alexander and Pfister 1995;Alexander et al 2000).…”
Section: Introductionmentioning
confidence: 99%